Trump-Putin Helsinki Summit : So Who Gained? - Cheang, Chris (2018)
The recent Helsinki meeting between Presidents Trump and Putin will be recorded in history as the commencement of a long process of stabilisation and normalisation of US-Russia relations, which hitherto have been described as worse than during the Cold War. In that respect, the meeting could be described as a limited success.